Incision of DNA–protein crosslinks by UvrABC nuclease suggests a potential repair pathway involving nucleotide excision repair - Minko, Irina G. (The National Academy of Sciences, 2002)
DNA–protein crosslinks (DPCs) arise in biological systems as a result of exposure to a variety of chemical and physical agents, many of which are known or suspected carcinogens. The biochemical pathways for the recognition and repair of these lesions are not well understood in part because of methodological difficulties in creating site-specific DPCs. Here, a strategy for obtaining site-specific DPCs is presented, and in vitro interactions of the Escherichia coli nucleotide excision repair (NER) UvrABC nuclease at sites of DPCs are investigated. To create site-specific DPCs, the catalytic chemistry of the T4 pyrimidine dimer glycosylase/apurinic/apyrimidinic site lyase (T4-pdg) has been exploited, namely, its ability to be covalently trapped to apurinic/apyrimidinic sites within duplex DNA under reducing conditions. Incubation of the DPCs with UvrABC proteins resulted in DNA incision at the 8th phosphate 5′ and the 5th and 6th phosphates 3′ to the protein-adducted site, generating as a major product of the reaction a 12-mer DNA fragment crosslinked with the protein. The incision occurred only in the presence of all three protein subunits, and no incisions were observed in the nondamaged complementary strand. The UvrABC nuclease incises DPCs with a moderate efficiency. The proper assembly and catalytic function of the NER complex on DNA containing a covalently attached 16-kDa protein suggest that the NER pathway may be involved in DPC repair and that at least some subset of DPCs can be removed by this mechanism without prior proteolytic degradation.